The effectiveness of a counseling program in developing social responsibility among preparatory students (Journal of the College of Basic Education, 2022)
Social responsibility is the individual's self-responsibility for the group before himself, before the group, and before God.The idea of ​​this study came through the researcher's sensitivity to the opinions of teachers, school principals, and parents of students, and many problems that students suffer from have been revealed. It is the starting and ending point in this process, hence the importance of the current research.